Acute Otitis due to Vibrio fluvialis after Swimming. (17th June 2012) - Chen, Ping-Jen; Tseng, Chi-Chou; Chan, Huan-Tee; Chao, Chien-Ming
Abstract : A 40-year-old female presented with purulent exudate through the left auditive duct and pain in the left ear region, which intensified during mastication. After collection of the pus from the left ear lesion, amoxicillin-clavulanic acid for seven days was prescribed for a presumed diagnosis of acute otitis. Four days later, the pus culture grew V. fluvialis which is further identified by API 20E identification system (bioMérieux). Following the successful completion of a course of antibiotics, the patient recovered completely and without complication. To the best of our knowledge, this is the first case of Vibrio fluvialis otitis after swimming in an immunocompetent patient.